Comparative Analysis of Animal Phraseological Units with Religious Component in Russian and Chinese - Lina Ding; Marina V. Lysyakova (RUDN Journal of Language Studies, Semiotics and Semantics, 2024)
The phraseological units analyzed in a comparative aspect reflect the peculiarities of the national worldview. The purpose of the study is to identify and compare the semantics and linguocultural properties of animal phraseological units with religious component in Russian and Chinese languages. The relevance of the topic is due to the insufficient study of idioms with the name of an animal component in the aspect of religious beliefs and traditions. The linguistic focus of this study is the phraseological units of the Russian language, reflecting the Christian and pagan ideas of the Russian people. The selection of the analyzed Chinese language material is due to the significant influence of Confucianism, Taoism, and Buddhism on Chinese culture. In the work, using a set of methods and techniques, such as linguocultural analysis, comparative analysis, and classification, the phraseological units of the Russian and Chinese languages with names of marine animals components birds, and terrestrial animals are studied. Similar and different figurative and symbolic meanings of animals are revealed in the two linguocultures. Discrepancies in the national and cultural connotations of animal images among speakers of Russian and Chinese languages against the background of religious and confessional differences have been established: the image of the same animal in different linguistic cultures generates different meanings. In addition to the discrepancies, Russian and Chinese idioms reveal semantic similarities due to the commonality of moral and ethical doctrines of Russian and Chinese speakers.